PAHAM KEAGAMAAN LOKAL (Studi Kasus Di Kasepuhan Ciptagelar) - Nuhrison M.Nuh (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2013)
The aim of this research are describing the relationship between the member of local religion with the state interests which embodied in policy and program as well as services and fulfillment of the citizenship rights in the administration of population. Specifically, this research sought to (a) exploring the existence of a local religion ideology and its adherents; (b) parsing and maping their social dynamics when they dealing with other identity and faiths, and (c) explaining and analyzing the factual situation regarding to services of population administration which influence to the right of citizenshipp, especially for local religion.